Intracranial Dural Arteriovenous Fistulas With Brainstem Engorgement: An Under-Recognized Entity in Diagnosis and Treatment - Hou, Kun; Li, Guichen; Qu, Lai; Liu, Hongping; Xu, Kan; Yu, Jinlu (Frontiers in Neurology, 2020)
BACKGROUND: In rare circumstances, patients with intracranial (dural arteriovenous fistulas) DAVFs could be complicated with brainstem engorgement, which might lead to delayed or false diagnosis and subsequent improper management. METHODS: On July 2th, 2019, a systematic search was conducted in the PubMed database for patients with intracranial DAVFs complicated with brainstem engorgement. RESULTS: Sixty-eight articles reporting of 86 patients were included for final analysis. The patients were aged from 20 to 76 years (57.10 ± 12.90, n=82). The female to male ratio was 0.68 (35:51). Thirty-three (40.2%, 33/82) patients were initially misdiagnosed as other diseases. The specific location distributions were cranio-cervical junction, cavernous sinus, superior petrosal sinus, transverse and/or sigmoid sinus, tentorium, and other sites in 27 (32.5%), 11 (13.2%), 9 (10.8%), 10 (12.0%), 21 (25.3%), and 5 (6.0%) patients, respectively. The Cognard classification of DAVFs were Ⅱ, Ⅲ, Ⅳ, and Ⅴ in 9 (10.7%, 9/84), 1 (1.2%, 1/84), 1 (1.2%, 1/84), and 73 (86.9%, 73/84) patients. Eighteen (22%, 18/82) patients were demonstrated to have stenosis or occlusion of the draining system distal to the fistula points. The mean follow-up period was 7.86 (n=74, range 0-60 months) months. Fifty-four (70.1%, 54/77) patients experienced a good recovery according to the mRS score. CONCLUSIONS: Intracranial DAVFs complicated with brainstem engorgement are rare entities. Initial misdiagnosis and delayed definite diagnosis are common in the past 3 decades. The treatment outcome is still unsatisfactory at present. Early awareness of this rare entity and efficiently utilizing the up to date investigations are of utmost importance.